Idiopathic hypereosinophilic syndrome presenting as monoplegia - Kushwah, Saraswati (BMJ Case Rep, 2019)
Idiopathic hypereosinophilic syndrome (IHES) is a rare disorder. It is characterised by persistent eosinophilia with eosinophil mediated tissue infiltration and organ dysfunction. Clinical features of IHES vary widely, as it may present with dermatological, pulmonary, gastrointestinal, cardiac or neurological symptoms. We hereby report a female patient who presented with sudden onset upper limb monoplegia and after thorough investigations she was diagnosed as a case of IHES. She was managed with corticosteroids and improved with same.